Relationship between the Transport Performance and Financial Coverage in Urban Public Transport in the Czech Republic - Kubik, Josef; Urbanek, Tomas (Communications - Scientific Letters of the University of Zilina, 2024)
The research presented aimed to compare the transportation performance, as measured by vehicle kilometers, to the operating costs incurred by thirteen transport companies in the Czech Republic from 2010 to 2019. This period was chosen to ensure that our research is not affected by the Covid-19 pandemic. The financial coverage of operating costs includes revenues from fares and compensations from city budgets. We utilized data from the annual reports of The Association of Transport Companies of the Czech Republic. Based on the obtained data, we confirmed a positive relationship between the city's population, the extent of transportation performance, and consequently, the total operating costs.
Keywords: urban public transport; sustainable urban mobility plan transport performance; financial coverage; statistical analyses